Personalised human shape modeling and behavior animation - Prakash, Edmond Cyril. (2008)
A variety of techniques currently exist for modeling natural objects. Automated human face modeling and animation has very recently appeared in papers and US patents. None of these techniques have been successful in realistic modeling of personalized shape or behavior. Two factors complicate the issue: 1. Modeling of individual humans with their own unique personalities has not been an easy task, mainly due to the enormous amount of time involved in capturing the characteristics of a human in a realistic form for each and every individual. 2. The other problem comes in adding life to the model, in terms of behavior such as movements (of the lips), physical deformation (of the cheek), as the information has been difficult to capture, more difficult to represent, and much more difficult to syn- thesize. This research project attempts to build a system and an apparatus to effectively model the shape and behavior of individual humans. The apparatus consists of a fast and accurate scanner to capture the shape. The system will have a multi-level hierarchical approach to capture and represent individual behavior and synthesize it for a variety of applications.